A new method for segmentation of microscopic blood cell images by using histogram based automatic thresholding - Coteli, Resul; Tuncer, Turker; Avci, Engin; Ustundag, Mehmet; Dogantekin, Esin; Dogantekin, Akif (Natl Inst Optoelectronics, 2017)
In this study, a novel thresholding algorithm based on histogram shape (TAHS) is proposed for determining the multiple thresholding. In the proposed thresholding method, histogram is divided into smaller windows with same size. In the proposed method, the biggest difference between pixel intensities is found. The proposed method is applied to blood cell images and is compared with Otsu method for a better validation. Advantage of the proposed method is that one or more thresholding points can be obtained. Therefore, objects with different spatial feature can be detected successfully. The experimental studies show that TAHS method gives satisfactory thresholding results.
Keywords: Image segmentation; Automatic image thresholding method; Microscopic blood cell images; Multiple thresholding method; Histogram shape